Efforts to Increase the Role of the Satsamapta Patrol Unit to Handle the Distribution of Alcohol in the Jurisdiction of the Kudus Police - Ardiansyah, Nico (Advances in Police Science Research Journal, 2024)
The final task raised with the problem of "Efforts to Increase the Role of the Satsamapta Patrol Unit to Handle the Distribution of Alcohol in the Legal Area of the Kudus Police". Writing this final project aims to describe the resources and implementation of the Satsamapta Patrol Unit in handling the distribution of alcohol in the jurisdiction of the Kudus Police. This study used a qualitative approach with the type of field research by interviewing informants, observing, and studying documents. In addition, the data used was also obtained from various references such as articles, journal books and online media news that were relevant to the problem variables discussed. This study uses management theory and SWOT analysis theory as well as several concepts that are relevant to the problem, namely the patrol concept based on Perkabaharkam Number 1 of 2017 concerning Patrols, the concept of effort, the concept of alcohol distribution. The Samapata Unit of the Kudus Police is the backbone of preventive police action in preventing criminal acts in the jurisdiction of the Kudus Police, especially the circulation of alcohol. In the implementation of patrols by the Samapta Polres Kudus patrol unit still found several deficiencies in terms of planning, organizing, implementing and supervising and not in accordance with the Patrol SOP which has been regulated in Perkabaharkam Number 1 Year 2017 concerning Patrol. In addition, there were factors that influenced both internally and externally, making the implementation of patrols by the Kudus Police Samapta Unit unable to be carried out optimally. On the other hand, the resources of the Patrol Unit Samapta Polres Kudus are still lacking in quality and quantity but the budget, facilities and infrastructure, methods and target/market have been fulfilled. Then in the implementation of patrols there were several conflicting findings at the planning, organizing, planning stages but at the monitoring stage the authors did not find anything contradictory.